Antimicrobial Potential of Endophytic Fungi From Artemisia argyi and Bioactive Metabolites From Diaporthe sp. AC1 - Gu, Haiping; Zhang, Shikai; Liu, Lin; Yang, Zhengyou; Zhao, Fengchun; Tian, Yuan (Frontiers in Microbiology, 2022)
Endophytic fungi of medicinal plants are important sources of active natural products. In this study, 26 fungi were isolated from Artemisia argyi, which were belonging to eight genera, Alternaria, Fusarium, Chaetomium, Phoma, Diaporthe, Trichoderma, Gibberella and Colletotrichum. The antimicrobial activities of all fungal extracts were tested by using cup-plate method against Staphylococcus aureus, Salmonella enteritidis and Fusarium graminearum. The results demonstrated that 25 extracts (96%) exhibited inhibitory activity against at least one of the tested pathogenic microorganisms. The strain Diaporthe sp. AC1, which showed good antimicrobial activity and high yield of crude extract from fermentation, was selected for study of secondary metabolites. The crude extract of strain AC1 was purified by silica gel column chromatography, Sephadex LH-20 gel column chromatography as well as HPLC, and finally a new compound phomopsolide G (1), together with three known phomopsolides (2~4) and four other known compounds (5~8) were obtained. The structures of the compounds were elucidated by NMR and/or HR-MS spectroscopy. Microdilution method and MTT colorimetry were used to determine the bioactivity of the compounds. The study demonstrated that the new compound 1 had moderate antifungal activity against F. graminearum, F. moniliforme and Botrytis cinerea and weak antibacterial activity against S. aureus. Compound 1 also showed weak cytotoxicity against HepG2, A549 and MDA-MB-231, with IC50 values of 89.91, 107.65 and 53.97 μM. Additionally, other compounds also exhibited antimicrobial and/or cytotoxic activities. The findings provided basis for searching for drug and agricultural lead compounds from A. argyi associated fungi resources.